Chronic pantothenic acid supplementation does not affect muscle coenzyme A content or cycling performance - Whitfield, J.; Harris, R. C.; Broad, E. M.; Patterson, A. K.; Ross, L. R.; Shaw, G.; Spriet, L. L.; Burke, L. M. (Applied Physiology, Nutrition, and Metabolism, 2021)
This study determined if supplementation with pantothenic acid (PA) for 16 weeks could increase skeletal muscle coenzyme A (CoASH) content and exercise performance. Trained male cyclists (n = 14) were matched into control or PA (6 g·day-1) groups. At 0, 4, 8, and 16 weeks, subjects performed an incremental time to exhaustion cycle with muscle biopsies taken prior to and following exercise. Prolonged PA supplementation did not change skeletal muscle CoASH and acetyl-CoA contents or exercise performance. Novelty: Supplementation with pantothenic acid for 16 weeks had no effect on skeletal muscle CoASH and acetyl-CoA content or exercise performance in trained male cyclists.